2015
DOI: 10.1002/app.42925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the maleation of lignosulfonate on the mechanical and thermal properties of lignosulfonate/poly(ε‐caprolactone) blends

Abstract: Maleated lignosulfonate (MLS) produced by esterification with maleic anhydride and unmodified lignosulfonate [in the form of lignosulfonic acid (LS)] were incorporated into poly(e-caprolactone) (PCL) via melt-blending. The obtained MLS/PCL composites and LS/PCL composites were characterized by Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), thermogravimetric (TG) analysis, and electronic universal testing. The FTIR and DSC results show that the interactions between MLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Esterified lignin applied in BPP composites has been studied the most in recent years. Lignin can be esterified by acid anhydride (maleic anhydride and butyric anhydride), , ester (methyl oleate), acyl chloride (10-undecenoyl chloride, oleoyl chloride, and dodecanoyl chloride fatty acid) , and successfully incorporated in PBAT, PLA, PBS, and PCL, respectively. Acid anhydride is the most common reagent to replace the hydroxyl group of lignin in solution, and esterified lignin performs with better miscibility with polyester.…”
Section: Chemical Modification Of Ligninmentioning
confidence: 99%
“…Esterified lignin applied in BPP composites has been studied the most in recent years. Lignin can be esterified by acid anhydride (maleic anhydride and butyric anhydride), , ester (methyl oleate), acyl chloride (10-undecenoyl chloride, oleoyl chloride, and dodecanoyl chloride fatty acid) , and successfully incorporated in PBAT, PLA, PBS, and PCL, respectively. Acid anhydride is the most common reagent to replace the hydroxyl group of lignin in solution, and esterified lignin performs with better miscibility with polyester.…”
Section: Chemical Modification Of Ligninmentioning
confidence: 99%
“…The authors also observed an increase in the blend rigidity resulting in higher Young’s modulus values for blends with 30–50 wt% of calcium lignosulfonate when compared with PBS. Wang et al (2016) used maleated lignosulfonate (MLS) produced by esterification with maleic anhydride and unmodified lignosulfonate incorporated into poly(e-caprolactone) (PCL) via melt-blending [ 16 ]. The authors also observed an enhancement in the mechanical properties of the blends in comparison with PCL.…”
Section: Introductionmentioning
confidence: 99%